Setting the agenda for collaboration in smallholder livestock producers in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Jimmy Smith, Director General, ILRI - talks of the importance of #AASW6 and setting the agenda for Livestock production for Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/